(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Multiple layers of clothing are known to increase thermal resistance and evaporative resistance. This study investigates the effect of wearing abaya, an Islamic outerwear stipulated for women, on thermal resistance performance assessed with a female thermal manikin. Tests were conducted at two climatic conditions. The first set was at 23 ° C and 50% RH as the dry condition and the second set was at 35 °C and 40% RH as the wet condition. Thermal resistance and evaporative resistance properties were measured by dressing a female thermal manikin in various ensembles of clothing within different types of abaya. The test results revealed that for all abaya combinations with daily wear, the manikin needed less heat to maintain the average skin temperature than with daily wear clothing alone. This study suggests that the abaya provided additional thermal and vapour resistance. Among the types of abaya evaluated, those worn on the head offered higher thermal resistance than those worn from the shoulder with tight sleeves. Marginal variations were also observed on the basis of the clothing worn under the abaya.